Persuasive technology using computers to change what we think and do - Fogg, B. J. (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2003)
Can computers change what you think and do? Can they motivate you to stop smoking, persuade you to buy insurance, or convince you to join the Army? "Yes, they can," says Dr. B.J. Fogg, director of the Persuasive Technology Lab at Stanford University. Fogg has coined the phrase "Captology"(an acronym for computers as persuasive technologies) to capture the domain of research, design, and applications of persuasive computers. In this thought-provoking book, based on nine years of research in captology, Dr. Fogg reveals how Web sites, software applications, and mobile devices can be used to change people's attitudes and behavior. Technology designers, marketers, researchers, consumersanyone who wants to leverage or simply understand the persuasive power of interactive technologywill appreciate the compelling insights and illuminating examples found inside. Persuasive technology can be controversialand it should be. Who will wield this power of digital influence? And to what end? Now is the time to survey the issues and explore the principles of persuasive technology, and B.J. Fogg has written this book to be your guide. * Filled with key term definitions in persuasive computing *Provides frameworks for understanding this domain *Describes real examples of persuasive technologies.
Foreword / Philip Zimbardo -- Preface -- Introduction: Persuasion in the digital age -- Overview of captology -- The functional triad : computers in persuasive roles -- Computers as persuasive tools -- Computers as persuasive media : simulation -- Computers as persuasive social actors -- Credibility and computers -- Credibility and the World Wide Web -- Increasing persuasion through mobility and connectivity -- The ethics of persuasive technology -- Captology : looking forward -- Appendix: Summary of principles.
Includes bibliographical references and index.
Keywords: Persuasion (Psychology) -- Computer programs; Human-computer interaction; Web -- Aspect social; Electronic books